Factors affecting technical efficiency of rubber smallholders in Negeri Sembilan, Malaysia - Abdulrahman, Aliyu; Abd. Latif, Ismail; Shamsudin, Mad Nasir; Mohd Nawi, Nolila (Canadian Center of Science and Education, 2017)
The main objective of the study was to figure out, identify and analyse the technical efficiency of rubber smallholders’ production in Negeri Sembilan, Malaysia. Multi-stage data collection procedures, comprising both purposive and random sampling techniques, were used. Using structured questionnaires, farm-level information with cross sectional data from five districts of Negeri Sembilan, were employed in the study. A parametric Stochastic Frontier Analysis (SFA), with a transcendental logarithmic (Translog) functional form, was used in the study. The descriptive statistics results revealed that, the mean rubber yield was 5465 kg while that of the seven inputs used include 1.2 ha, 602.7, 2.33, 363.6 kg, 13.0 lit, 13.2 man days and 2.47 respectively for farm size, task, farm tools, fertilizer, herbicides, labour and rubber clones.The inferential statistics showed that, the mean technical efficiency was found to be 0.73 with a standard deviation of 0.089. Thus, this translates that 27% accounted for technical inefficiency. Both the sigma square and gamma coefficients were found to be statistically significant at 1% level. The Log Likelihood Function (LLF) and the Log Rati (LR) test were found to be respectively 167.7 and 34.07. The results further revealed that, although none of the farms were found to be on the frontier, however, 9 farms were very near the frontier with efficiency score range between 0.90-0.99. And twenty (20) firms have range 0.80-0.90. Race, Tapping experience, household number and extension agent’s visits were found to be technically significant and are thus critical in determining technical efficiency of rubber smallholders in Negeri Sembilan, Malaysia.